2019
DOI: 10.35490/ec3.2019.163
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain in construction logistics: state-of-art, constructability, and the advent of a new digital business model in Sweden

Abstract: Research on blockchain technology implementation within civil engineering is quickly emerging. The use of blockchain for the integration of the material and economic flows within construction supply chain-thus creating a new digital business model for the related actors-to enhance a construction project's production, logistics management, and constructability, has been only scarcely investigated. In this paper, this shortage is documented through a comprehensive literature review. Then, the potential of Swedis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The review of the literature reveals a need for increased attention on the integration between physical and financial supply chains (Kifokeris and Koch 2019). The research landscape has remained mostly theoretical (Darabseh and Martins 2020;Kasten 2020) and lacks validation of usability (Hijazi et al 2019).…”
Section: Applications Of Smart Contract For Cash Flow Managementmentioning
confidence: 99%
“…The review of the literature reveals a need for increased attention on the integration between physical and financial supply chains (Kifokeris and Koch 2019). The research landscape has remained mostly theoretical (Darabseh and Martins 2020;Kasten 2020) and lacks validation of usability (Hijazi et al 2019).…”
Section: Applications Of Smart Contract For Cash Flow Managementmentioning
confidence: 99%
“…Shojaei [29] and Dounas et al [57] claimed that the blockchain application environment was not fully formed, owing to a lack of empirical cases. Li et al [4] and Kifokeris and Koch [77] showed that the application of blockchain in the AEC industry remains in its infancy. These articles emphasised the absence of clear legislation in smart-contract management and enforcement.…”
Section: Environmental Challengesmentioning
confidence: 99%
“…For the Swedish context, subsequent studies by Kifokeris and Koch (2019a,b,c; have gradually investigated the integration of the material, economic and information flows in the construction supply chain, through a blockchain solution forming part of the value proposition in logistic consultants' business models. In particular, Kifokeris and Koch (2019a) investigated the suitability of Swedish construction supply chains and logistics for the accommodation of a blockchain solution integrating the logistics flows, involving independent logistics consultants (usually hired by public clients in building projects) that can incorporate such a solution in their digital business model; the study then proceeded with a preliminary mapping of such consultancies operating in Sweden. In Kifokeris and Koch (2019b), the scientific perspective of sociomateriality was initially introduced in relation to a potential blockchain solution for integrated logistics flows, and the power shifts that such a solution would bring in constellations of supply chain actors in the Swedish context, was discussed; these constellations included the typical case of large contractors internalizing logistics services, the atypical case of using independent logistics consultants, and the emergent case of third-party actors offering dedicated digital building logistics services.…”
Section: Literature Reviewmentioning
confidence: 99%